Sunshine Trading: Flashes of Trading Intent at the Nasdaq - Johannes A. Skjeltorp; Elvira Sojli; Wing Wah Tham (Norges Bank, 2011)
We use the introduction and the subsequent removal of the flash order facility (an actionable indication of interest, IOI) from Nasdaq as a natural experiment to investigate the impact of voluntary disclosure of trading intent on market quality. We find that flash orders significantly improve liquidity in Nasdaq. In addition overall market quality improves substantially when the flash functionality is introduced and deteriorates when it is removed.
hdl:11250/2496942
Keywords: G10; G20; G14; 330; IOI; actionable indication of interest; flash orders; high frequency trading; market quality; market transparency; sunshine trading